Analisis Personal Branding: Kesuksesan Pembawaan Cerita Kisah Horor Wawak Nadia Omara di YouTube - Dinar Cahya Nurani; Lelita Azaria Rahmadiva (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Nadia Omara is recognized as a prominent YouTuber in the horror storytelling genre through her unique series Kisah Horor Wawak (KHW). This series stands out with its distinctive style, setting her apart from other horror storytellers. Her strong regional accent and storytelling style which is both entertaining and suspenseful make her a compelling subject of study. This research aims to explore how Nadia Omara applies personal branding strategies to achieve success in delivering horror narratives on her YouTube channel. A qualitative approach is used, employing methods such as observation, media analysis, and documentation. Data analysis is conducted using source triangulation and validity triangulation to ensure accuracy and depth. The findings reveal that Nadia’s consistent use of personal branding based on the eight elements of Montoya’s (2003) namely Specialization, Leadership, Personality, Difference, Visibility, Unity, Resilience and Good Name, theory plays a crucial role in her success. She has built a strong, authentic, and trustworthy image that resonates with the audience, establishing her as a well-known horror storyteller on YouTube. This study focuses on the analysis of three of her most viewed KHW videos. Future research is recommended to examine Nadia’s content from different perspectives, such as audience analysis, to further assess the effectiveness of her personal branding.